Sequential muscle activation in the hemiparetic arm - C. Mucha (AOSIS, 2004)
This study investigated the chronological activation sequence of multiple joint movements of the hemiparetic arm in patients with central hemiparesis compared to healthy test subjects.Twelve patients with central hemiparesis and eight healthy control subjects were studied. First, in rapid abduction movement of the upper limb, the electromyographic activities of the middle part of the deltoid muscle, the brachial biceps muscle and the extensor muscles of the fingers, were registered. Second, in rapid flexion of the arm, the electromyographic activities of the ventral part of the deltoid muscle, the brachial biceps muscle and the superficial flexor muscles of the fingers, were measured. From the EMG data registered, activation duration, activation latency and the innervation sequence were determined and compared between the patient group and the control group. In the patient group, a significant prolongation of the activation duration was shown only in abduction. However, the activation latency was significantly prolonged in both movements compared to healthy test subjects. In the innervation sequences, a simultaneous activation was most frequently shown in healthy subjects. In healthy subjects, the deltoid muscle also usually functioned as leading muscle, whereas there was sometimes a shift distally to the brachial biceps muscle in the hemiparetic patients. The speed of rapid multiple joint movements in hemiparetic extremities seems to be unaffected in certain movements (anteversion), in others (abduction) it seems to be significantly reduced. This, as well as the fact that the activation latency is significantly longer in the hemiparetic limbs should be taken into consideration when choosing rehabilitation exercises.